Defect Repair Efforts in Bone Plate Product Quality Control Using Six Sigma (Case Study: PT ABC) - Farrel Azriel Septrianto; Dwi Sukma Donoriyanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to identify and reduce Bone Plate product defects at PT Risa Implantama, a domestic orthopedic and traumatology implant manufacturer. Using Six Sigma methodology, this research applies the DMAIC (Define, Measure, Analyze, Improve, and Control) stages to analyze Bone Plate production data from January to December 2023. The analysis results show that the most dominant defect is in the hole diameter with a total of 114 defects. The resulting DPMO (Defects Per Million Opportunities) value is 7474, with an average sigma level of 3,94. Proposed improvements include improving raw material quality control, operator training, and routine machine maintenance to improve product quality and approach the Sigma level 6 target.